Implementasi Kebijakan Standar Operasional Prosedur Pelayanan Perizinan Terpadu Pada Badan Penanaman Modal Dan Perizinan Terpadu Dalam Meningkatkan Kepuasan Masyarakat Di Kabupaten Sumedang Provinsi Jawa Barat - Christofel Tuba Lay Bahas (Institut Pemerintahan Dalam Negeri (IPDN), 2020)
This study aims to find out how the implementation of standard operational policies for integrated licensing service procedures in investment agencies and integrated licensing in increasing public satisfaction, what are the inhibiting factors faced in implementing the standard operational policy procedures for integrated licensing services in investment agencies and integrated licensing in improving community satisfaction and the efforts made to overcome the obstacles faced. The theory used in this study, using the implementation theory developed by Hamdi, the implementation of policies is described in three aspects, namely 1) Productivity; 2) Linearity; 3) Efficiency; This research method uses descriptive qualitative research methods with an inductive approach which aims to describe the phenomena associated with the scope of research. Sources of data used are person (person), place (place), paper (data). For data and information retrieval is done using observation techniques, in-depth interviews and document review. Based on the results of the research that 1) the implementation of standard operational policy procedures for integrated licensing services at the investment agency and integrated licensing in Sumedang Regency in increasing community satisfaction has not been fully implemented due to the implementation of policies not linear and the implementation of policies that are not efficient 2) the inhibiting factors for the implementation of standard operating procedures for licensing service policies are the contents of the policies are not aligned, the behavior of service officers is not aligned, the contribution of the community is weak, the lack of use of technology in services, 3) the efforts made to overcome the inhibiting factors are formulating new policies, providing motivation, disseminating information about SOPs, formulating the concept of the official BPMPT website.